Volunteerism from Islamic perspective - Sulaiman, Kabuye Uthman (2011)
Volunteerism is a great virtue that is grounded in the teachings of both revealed and non-revealed religions and in all cultures. Since time immemorial, people have been spending time and money to help others without any expectation of compensation. All Prophets were volunteers and they emphatically stressed the need for volunteerism. Billions of hours are devoted to volunteer activities and some world leaders have also called upon their subjects to volunteer their time and money to help others. The aim of this work is to highlight the concept of volunteerism from the Islamic perspective. No religion or law gives volunteerism as much importance as Islam does. Islam encourages its followers to voluntarily share their time, wealth, knowledge and acts of kindness with others. The work is divided into two sections dealing with discussions on the meaning of volunteerism, its different forms and ethics.